Digital Literacy 2013
DOI: 10.4018/978-1-4666-1852-7.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Millennials are Digital Natives?

Abstract: The abundance of opinions about Millennials has made it very difficult to separate reality from conjecture, especially with regard to the suppositions made about their propensity towards technology. Labeled as digital natives, Millennials are thought to possess learning traits never before seen as a result of growing up in the digital information age. In this chapter, we present the findings of a study in which postsecondary students (N = 580) were surveyed to quantitatively investigate the differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Millennials, 72 million Americans born between 1981and 1996(Fry 2020, are the most ethnically and culturally diverse age cohort in the United States; nearly 25% of this age group is African American and 18% is Hispanic (Licsandru and Cui 2019). Generation Z, individuals born after 1996, are also digital natives and heavy users of social media (Dacosta et al 2013;Thigpen and Tyson 2021). Whitinger and Cohen (2021) reported that youths (classified as persons 18-34 years old) are driving a large portion of the houseplant purchases and make the most online plant purchases of any age group.…”
mentioning
confidence: 99%
“…Millennials, 72 million Americans born between 1981and 1996(Fry 2020, are the most ethnically and culturally diverse age cohort in the United States; nearly 25% of this age group is African American and 18% is Hispanic (Licsandru and Cui 2019). Generation Z, individuals born after 1996, are also digital natives and heavy users of social media (Dacosta et al 2013;Thigpen and Tyson 2021). Whitinger and Cohen (2021) reported that youths (classified as persons 18-34 years old) are driving a large portion of the houseplant purchases and make the most online plant purchases of any age group.…”
mentioning
confidence: 99%